2018
DOI: 10.1097/yco.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

National Institute on Drug Abuse International Program

Abstract: Purpose of review For more than 25 years, the National Institute on Drug Abuse (NIDA) has supported research-training programs, establishing a global research network and expanding the knowledge base on substance use disorders. International research to inform approaches to opioid addiction is particularly important and relevant to the United States, where opioid misuse, addiction, and overdose constitute an emerging public health crisis. This article summarizes the NIDA International Program and illustrates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Opioid maintenance treatment (OMT) programs using Methadone, the most researched substitute for heroin, are life-saving as they keep people in treatment programs and reduce heroin use (Marotta and McCullagh 2018;Mattick et al 2009). Internationally, authorities endorse the use of OMT (Gust and McCormally 2018). In Sweden, the National Board of Health and Welfare recommends OMT as the first-line choice of treatment for heroin addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Opioid maintenance treatment (OMT) programs using Methadone, the most researched substitute for heroin, are life-saving as they keep people in treatment programs and reduce heroin use (Marotta and McCullagh 2018;Mattick et al 2009). Internationally, authorities endorse the use of OMT (Gust and McCormally 2018). In Sweden, the National Board of Health and Welfare recommends OMT as the first-line choice of treatment for heroin addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Opioids use lead to opioids use disorder impacting heavily on a country's economy through medical illness, loss of productivity, injuries and fatalities from automobile and other accidents, overdose inflicted deaths, suicides and violence (UNODC, 2019c). In 2017 alone, the study by Gust and Mccormally (2018) revealed that 72,000 overdose deaths occurred and 2.1 million Americans aged 12 years and older met the diagnosis of OUD. National Institute on Drug Abuse International program (NIDA, 2018b) on advancing addiction science findings reveal that opioid misuse, addiction and overdose constitute an emerging health crisis.…”
Section: E Opioidsmentioning
confidence: 99%
“…18,[26][27][28]33,34,37 The NIDA International Program has consistently monitored fellowship outcomes internally and has previously reported on fellowship outcomes in peer-reviewed journals and textbooks. [38][39][40][41][42] However, this is the first comprehensive effort to assess the NIDA INVEST postdoctoral fellowships from the combined perspectives of career outcomes, migration patterns, publications, cost per publication, and funding.…”
Section: Evaluating the Nida Invest Postdoctoral Fellowshipsmentioning
confidence: 99%
“…Following the protocol for a publication analysis that we published in 2018, 39 we conducted individual searches in PubMed for articles coauthored by former NIDA INVEST fellows during 2018 and 2019. A total of 746 publications were identified.…”
Section: Career Outcomesmentioning
confidence: 99%